Orotracheal administration of contrast agents: a new protocol for brain tumor targeting. (29th April 2015) - Bianchi, Andrea; Moncelet, Damien; Lux, François; Plissonneau, Marie; Rizzitelli, Silvia; Ribot, Emeline Julie; Tassali, Nawal; Bouchaud, Véronique; Tillement, Olivier; Voisin, Pierre; Crémillieux, Yannick
<x xml:space="preserve">Abstract</x> The development of new non‐invasive diagnostic and therapeutic approaches is of paramount importance in order to improve the outcome of patients with glioblastoma (GBM). In this work we investigated a completely non‐invasive pre‐clinical protocol to effectively target and detect brain tumors through the orotracheal route, using ultra‐small nanoparticles (USRPs) and MRI. A mouse model of GBM was developed. In vivo MRI acquisitions were performed before and after intravenous or orotracheal administration of the nanoparticles to identify and segment the tumor. The accumulation of the nanoparticles in neoplastic lesions was assessed ex vivo through fluorescence microscopy. Before the administration of contrast agents, MR images allowed the identification of the presence of abnormal brain tissue in 73% of animals. After orotracheal or intravenous administration of USRPs, in all the mice an excellent co‐localization of the position of the tumor with MRI and histology was observed. The elimination time of the USRPs from the tumor after the orotracheal administration was approximately 70% longer compared with intravenous injection. MRI and USRPs were shown to be powerful imaging tools able to detect, quantify and longitudinally monitor the development of GBMs. The absence of ionizing radiation and high resolution of MRI, along with the complete non‐invasiveness and good reproducibility of the proposed protocol, make this technique potentially translatable to humans. To our knowledge, this is the first time that the advantages of a needle‐free orotracheal administration route have been demonstrated for the investigation of the pathomorphological changes due to GBMs. Copyright © 2015 John Wiley & Sons, Ltd.